Reference Point Adaptation and Disposition Effect: Evidence from Institutional Trading - CHIYACHANTANA, Chiraphol N. (Institutional Knowledge at Singapore Management University, 2010)
Using a large proprietary database of institutional trades, we investigate whether, and to what extent, the dynamic adaptation of reference point translates into variations in the disposition effect, and establish three key results. First, the propensity to realize losses declines sharply with the magnitude of prior losses due to insufficient adaptation of reference point. Second, recent adverse information accelerates investors’ adaptation to price depreciation and increases investors’ willingness to realize losses. Finally, a priori of losing money in highly speculative investments decreases investors’ aversion to realize losses. Collectively, the findings suggest that both prior outcomes and recent expectations contribute to the reference point adaptation and the variations in disposition effect.